Analysis of heavy metal pollution of iron (Fe) and zinc (Zn) in soil at Putri Cempo Landfill, Indonesia - Hawali Abdul Matin Hashfi; Rachmawati Siti; Sastrani Naluri Allobua Brighia; Chesta Ricky Adabi; Nisrina Shofi Izdihar; Nur’l Farida Luqyana Destiani; Firdausi Eyda; Fabiola Candraningtyas Callista (BIO Web of Conferences)
The correlation between heavy metals and environmental pollution is undeniable. This is due to the presence of various types of heavy metals and an increase in the value of heavy metal content, which directly results in a decrease in soil fertility. This study aims to determine the content of heavy metals Fe and Zn in the soil of Putri Cempo Landfill. Analysis of heavy metal substances Fe and Zn is focused because basically both substances are substances that are commonly found in the soil. The method used to measure Fe and Zn is the Atomic Absorption Spectrometry (AAS) method The parameters tested were Iron (Fe) 0, 0.5, 1, 2, 3, 5 ppm while for Zinc (Zn) 0, 0.05, 0.1, 0.5, 1.5, 2 ppm. The sample was then wet destroyed and then tested. Analysis of the results of the equation of the line on the curve obtained a linear regression of the relationship between absorbance and concentration of the standard Fe solution is y = 0.1431 and x = 4.184173 where y is the absorbance value and x is the Fe content. R2 value 1 (R2 = 0.9992). Linear regression of the relationship between absorbance and concentration of standard Fe solution is y = 0.1431 and x = 4.184173 mg/Kg, where y is the absorbance value and x is the Fe content. Putri Cempo Landfill soil is still below the specified threshold value. Based on these results, the land in TP Putri Cempo is still considered good for use by human activities, agriculture and for ecology.